The Effect of a Holistic School Improvement Model in Enhancing School Effectiveness in Oman - Abdo Mohamed Al-Mekhlafi; Mohamed El Tahir Osman (UUM Press, 2019)
Purpose - This study examined the impact of a holistic school improvement model on overall school effectiveness, More specifically, it attempted to answer two questions: 1) Are there any significant differences in school performance between the control group and the experimental group before and after the experiment? 2) Is there any significant improvement in the experimental group school effectiveness before and after the experiment? Methodology - As a part of a four-year longitudinal research project, the study used a quasi experimental research design to examine the impact of a holistic school improvement model on enhancing overall school effectiveness in Oman. The sample consisted of 16 intact classes selected from 8 schools (4 experimental and 4 control groups), with a total of 2378 students (1157 from grade nine classes and 1221 from grade seven classes). The experimental group schools were exposed to a wide range of school improvement activities within a four-year period. A series of workshops on activating the 13 elements of the Innovation Sustainability Wheel (ISW) were delivered to all administrators and teachers at the target experimental group schools, in addition to empowering students through enrichment programs in five subject areas. Data was collected from the Omani Ministry of Education school performance indicators, which included five subject matter achievement tests aggregated over three years. Findings - The study revealed significant differences in overall school performance across the four years between the control and experimental schools, in favour of the experimental group. Moreover, a significant progression of school effectiveness was observed in the two grade levels of the experimental group. Significance - The findings are significant in terms of providing educational systems with a workable mechanism for identifying key areas of weaknesses and means of improvement; establishing a chain of actions for activating all interrelated elements that act as driving forces for sustainable change; ensuring that the indicators of school improvement should include both operational processes and studentsâ€™ learning outcomes; and contributing to the knowledge base in the area of school improvement in terms of a research-based model that has potential implications for practitioners and policy makers.